Efektivitas Penghapusan Barang Milik Daerah Pada Keuangan di Sekretariat DPRD Kota Bandung - Vanessa Wulandari Oksantiarozen; Herabudin Herabudin; Herry Sutanto (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
The deletion of property belonging to this area is carried out in the absence of the ruler or the power of the user of the goods who has been transferred to the ownership of the destruction that has occurred or for other reasons, this deletion is carried out in the presence of a regional head who makes a decision and acts as the manager of the goods. Regional ownership (BMD) is a problem that is considered insignificant. The purpose of this study was to determine the effectiveness of the elimination of regional property on finance at the Secretariat of the DPRD City of Bandung, the obstacles and efforts to minimize these problems or obstacles. The theory used by Dunn for adequacy and responsiveness. Researchers used a qualitative research method with a descriptive approach. Primary data sources used were field surveys and interviews; secondary data used is directly from the Head of Asset and Household Section and Asset and Household Staff. The data analysis technique used was the Miles and Hubberman model. The results of this study show that the effectiveness of the elimination of regional property in finance is eliminated by means of an auction / tender; barriers to delivery of goods are severely damaged, lost or unknown, the goods to be written off are no longer intact; efforts have been made to minimize these obstacles or problems. namely the same as the explanation in the first point by way of the auction / tender.